Budaya Minangkabau Dalam Tradisi Duduk Induk-Induk Di Nagari Ujung Gading - Mariska, Yohana; Arifinsyah (LPPM Universitas 17 Agustus 1945 Semarang, 2025)
The custom of sitting on the parent-parents is discussed in this journal by the residents of Ujung Gading Village, a mixed-ethnic community that includes both Mandailing and Minangkabau residents. This duduk induk-induk custom, which is typically referred to as markumpul hepeng (money collection), is a mutually supportive attitude and a custom that is practiced by community organizations to aid the host in paying for the wedding. This publication looks at or investigates ways to comprehend and research Minang culture in Ujung Gading overall. Particularly in the duduk induk-induk procedures, it can also serve as a source of information and research for the advancement of linguistic science in the study of the duduk induk-induk tradition and comprehend it from an Islamic standpoint. Using qualitative data analysis methods, information was gathered via literature reviews, interviews, and documentation. The study's findings demonstrate that the coaching provided by traditional leaders—namely, putir, ninik mamak, and datuk kinayah—took the form of discussion.